Genre, Boundary Drawing and the Classificatory Imagination. (June 2013) - Beer, David
This article suggests that the vitality of genre, and particularly music genre, is often missing from social and cultural research. This is despite its central presence as a structural force within increasingly popular forms of field analysis. To deal with this absence, the article draws upon conceptual material on everyday forms of classification and new forms of digital data. It is argued that the concept of a classificatory imagination might be used to develop a more contingent and transient vision of genre as a form of everyday cultural classification or as a structuring force in cultural fields. The article describes three problems facing cultural sociology in its use of genre categories. Two are briefly presented whilst the third is developed through a case study of hip hop. The article concludes with some reflections upon what this reveals about cultural boundary drawing and the impact of decentralized media upon genre formation.